Restrictive compared with liberal red cell transfusion strategies in cardiac surgery: a meta-analysis - Shehata, Nadine (Eur Heart J, 2019)
AIMS: To determine whether a restrictive strategy of red blood cell (RBC) transfusion at lower haemoglobin concentrations is inferior to a liberal strategy of RBC transfusion at higher haemoglobin concentrations in patients undergoing cardiac surgery. METHODS AND RESULTS: We conducted a systematic review, meta-analysis, and trial sequential analysis of randomized controlled trials of the effect of restrictive and liberal RBC transfusion strategies on mortality within 30 days of surgery as the primary outcome. Secondary outcomes were those potentially resulting from anaemia-induced tissue hypoxia and transfusion outcomes. We searched the electronic databases MEDLINE, EMBASE, and the Cochrane Library until 17 November 2017. Thirteen trials were included. The risk ratio (RR) of mortality derived from 4545 patients assigned to a restrictive strategy when compared with 4547 transfused according to a liberal strategy was 0.96 [95% confidence interval (CI) 0.76–1.21, I(2) = 0]. A restrictive strategy did not have a statistically significant effect on the risk of myocardial infarction (RR 1.01, 95% CI 0.81–1.26; I(2)=0), stroke (RR 0.93, 95% CI 0.68–1.27, I(2) = 0), renal failure (RR 0.96, 95% CI 0.76–1.20, I(2) = 0), or infection (RR 1.12, 95% CI 0.98–1.29, I(2) = 0). Subgroup analysis of adult and paediatric trials did not show a significant interaction. At approximately 70% of the critical information size, the meta-analysis of mortality crossed the futility boundary for inferiority of the restrictive strategy. CONCLUSION: The current evidence does not support the notion that restrictive RBC transfusion strategies are inferior to liberal RBC strategies in patients undergoing cardiac surgery.